2013
DOI: 10.4172/1948-593x.1000073
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Neuro Endocrinological Changes and Oxidative Stress during Chronic Lead Intoxication

Abstract: The dangerous effect of lead was evaluated in male mice exposed to lead acetate at dose 2000 and 4000 ppm in drinking water, as well as subjects working in fields with high lead levels. Lead exposure exhibited marked decrease in body weight, as well as in hematological parameters such as hemoglobin content, hematocrit percent, erythrocytes and leucocytes count. In addition, there was a disruptive effect on neurological and endocrinological systems reflected by alterations in T3, T4, testosterone and cortisol h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…The most widely test used for the oxidative stress is the measurement of MDA, a product of lipid peroxidation by the Thiobarbituric Acid Reacting Substance Assay. Ours results showed that lipid peroxidation level was increased in both Cerebrum and Cerebellum after an exposure to lead acetate during gestation and lactation which was in accordance with the study of [41].The high levels of MDA recorded in brain of intoxicated rats may be explained by alteration of lipid membranes attributed to lead which consequently caused an alteration in membranes integrity , permeability and functions [42]; these data correlate with the sensitivity of brain to lead intoxication during development until Blood-Brain -Barrier (BBB) is fully functional [43]. It has been reported that lead is a potential agent for inducing oxidative stress by production of ROS.…”
Section: Lipid Peroxidation and Catalase Activitysupporting
confidence: 91%
“…The most widely test used for the oxidative stress is the measurement of MDA, a product of lipid peroxidation by the Thiobarbituric Acid Reacting Substance Assay. Ours results showed that lipid peroxidation level was increased in both Cerebrum and Cerebellum after an exposure to lead acetate during gestation and lactation which was in accordance with the study of [41].The high levels of MDA recorded in brain of intoxicated rats may be explained by alteration of lipid membranes attributed to lead which consequently caused an alteration in membranes integrity , permeability and functions [42]; these data correlate with the sensitivity of brain to lead intoxication during development until Blood-Brain -Barrier (BBB) is fully functional [43]. It has been reported that lead is a potential agent for inducing oxidative stress by production of ROS.…”
Section: Lipid Peroxidation and Catalase Activitysupporting
confidence: 91%